2013
DOI: 10.1038/icb.2013.17
|View full text |Cite
|
Sign up to set email alerts
|

NKG2D CAR T‐cell therapy inhibits the growth of NKG2D ligand heterogeneous tumors

Abstract: Tumor heterogeneity presents a substantial barrier to increasing clinical responses mediated by targeted therapies. Broadening the immune response elicited by treatments that target a single antigen is necessary for the elimination of tumor variants that fail to express the targeted antigen. In this study, it is shown that adoptive transfer of T cells bearing a chimeric antigen receptor (CAR) inhibited the growth of target-expressing and –deficient tumor cells within ovarian and lymphoma tumors. Mice bearing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 34 publications
0
54
0
Order By: Relevance
“…While NKG2D is an activating receptor on natural killer (NK) cells, it functions primarily as a costimulatory receptor on activated CD8+ T cells [5][6][7][12][13][14][15] . In both murine and human T cells, signaling through the NKG2D receptor is mediated through an adaptor protein, DAP10 8,13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While NKG2D is an activating receptor on natural killer (NK) cells, it functions primarily as a costimulatory receptor on activated CD8+ T cells [5][6][7][12][13][14][15] . In both murine and human T cells, signaling through the NKG2D receptor is mediated through an adaptor protein, DAP10 8,13 .…”
Section: Introductionmentioning
confidence: 99%
“…One method of generating CARs fuses native proteins, which naturally ligate proteins on the surface of tumor cells, with the intracellular signaling domains required to induce T cell activation. Ligands for the natural killer group 2 member D (NKG2D) receptor are numerous and are frequently upregulated on many cancer types [5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…The differences in kinetics seen in our study may have occurred for several reasons including differences in CAR T-cell dose, preconditioning regimes, distribution of target antigen in normal tissue, and murine strain variability. 51 Additionally, several groups have observed safe therapeutic targeting of fibroblast activating protein in murine models, 52,53 suggesting that differences in the therapy could allow for safe targeting by CAR T cells. Future studies with regulatable B7-H4 CARs could evaluate T-cell trafficking, kinetics, and impact on tissue utilizing withdrawal of B7-H4 CAR treatment prior to induction of lethal toxicity.…”
Section: Model To Interrogate Questions Addressing B7-h4's Function Amentioning
confidence: 99%
“…Fully human anti-B7-H4 scFv sequences 14,53 were amplified via polymerase chain reaction from plasmids containing each soluble scFv sequence using the following primers:…”
Section: Construction Of the B7-h4 Car Vectorsmentioning
confidence: 99%
“…CAR T cells express tumor-antigen specific antibody fragments on their surface, fused to intracellular activation proteins ( e.g., CD3ζ, 4-1BB, OX40) and recognize antigen independent of MHC. A preclinical study showed NKG2D-specific CAR T cells provide protection and establish memory against distinct OC tumors where only 7% cells express NKG2D [106] . Despite inducing complete remissions in leukemia patients, the efficacy of CAR T cells in solid tumors has been more limited due to inefficient tumor homing.…”
Section: Treatmentmentioning
confidence: 99%